(untitled) (International Journal of Physiotherapy, 2017)
Background: Many therapeutic uses for Pulsed magnetic fields have been extensively studied. Beneficial effects on the musculoskeletal system were established including bone healing, pain relief, and inflammatory conditions. The study aimed at investigating the possible effects of the pulsed magnetic field on quadriceps muscle torque, hamstring muscle torque and knee proprioception accuracy in athletic subjects. Methods: A randomized controlled trial which was carried out at the Faculty of Medical Rehabilitation Sciences, Taibah University, Saudi Arabia. Thirty healthy male athletic subjects, aging from 18 – 24 years were divided into two groups, study group (15 subjects) & control group (15 subjects). The pulsed magnetic field was applied for subjects of intervention group, while control group participants received sham pulsed magnetic field for 12 sessions over a period of 4 weeks. Quadriceps muscle torque, hamstring muscle torque & knee proprioception accuracy were measured before & after treatment for all participants using Biodex system 4 pro isokinetic dynamometer. Results: Multiway ANOVA was carried out to detect any significant differences within and between groups. Statistically significant differences between study and control groups were found after pulsed magnetic field application in quadriceps peak torque (at 60 and 120deg/sec) & hamstring peak torque (at 60 and 120deg/sec) and in knee proprioception accuracy (p-value was 0.004, 0.0001, 0.02, 0.03, 0.0001 respectively). Conclusion: Pulsed magnetic field has beneficial effects on quadriceps muscle peak torque, hamstring muscle peak torque and knee proprioception accuracy in healthy athletic subjects and can be advised as an adjunctive tool in rehabilitation programs.